Acantholimon ibrahimii (Plumbaginaceae), a new species of A. section Staticopsis from the Mediterranean part of Turkey - Akaydin, Galip (Phytotaxa, 2018)
A new species, Acantholimon ibrahimii Akaydın, is described, illustrated and discussed in comparison with its close relative A. davisii. The new species is distinguished from the latter species mainly by the generative organs (namely the inflorescence types and petals colour), habitat type and ecological behaviour. Data are also reported on the conservation status of A. ibrahimii, which is suggested to be labelled as EN according to the IUCN categories. Furthermore, a revised key to the Turkish Acantholimon species of A. sect. Staticopsis with spike laxly distichous and scape much longer than leaves is presented.